Management Practices to Control Tropical Soda Apple - Jeff Mullahey; Patrick Hogue; Jason Ferrell; Brent Sellers (EDIS, 2006)
Revised! SS-AGR-130, a 3-page fact sheet by Jeff Mullahey, Pat Hogue, Jason Ferrell, and Brent Sellers, explains to cattlemen the basics of Prevention, Detection, and Control of Tropical Soda Apple. This version includes updated herbicide recommendations and a list of resources for further information. Published by the UF Department of Agronomy, August 2006.